Another World… Inside This One - Brian Treanor (Diakrisis)
Continental philosophy has long been concerned with the question of transcendence, a fact attributable in part to the historical significance of phenomenology and the legacy of debates surrounding transcendental idealism, the epoche, the status of the world and of other people, and, at least for some philosophers, the question of God. The question takes different forms in Husserl, Heidegger, Merleau-Ponty, Sartre, Levinas, Derrida, Marion, and others working in this tradition, but it remains an abiding concern for each of them. Over time the persistence of this issue has formed a body of work that constitutes a kind of center of gravity—one among several—that characterizes continental thinking.